2016
DOI: 10.1111/echo.13333
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative echocardiography‐derived right ventricle function parameters and early outcomes after tetralogy of Fallot repair in mid‐childhood: a single‐center, prospective observational study

Abstract: Among the RV function parameters studied, RV FAC best predicted the early outcome variables after TOF repair, followed by TAPSE while lateral tricuspid annular velocity S' being the least predictive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…This compares favourably to the results of Raj. et al and Waqar et al, who reported moderate or severe pulmonary insufficiency postoperatively in 56% and 37.1% of their patients, respectively, even though the rates of TAP repair in their studies were very similar to ours [14,15].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This compares favourably to the results of Raj. et al and Waqar et al, who reported moderate or severe pulmonary insufficiency postoperatively in 56% and 37.1% of their patients, respectively, even though the rates of TAP repair in their studies were very similar to ours [14,15].…”
Section: Discussionsupporting
confidence: 73%
“…Heinisch et al reported an exceedingly high rate of valve preservation in their cohort at 96%, which they attributed to unusually favourable pulmonary valve morphology and pulmonary annulus size in almost all of their patients [9]. In the other studies of complete repair of TOF in children older than one year of age, the rate of valve-preserving surgery was comparable to the rate in our study, ranging from 30% to 66.5% [8,[13][14][15]. The reported rate of valve preservation among children undergoing complete repair in infancy ranges from 22% to 80%, which is also comparable to our cohort [18][19][20][21].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Lower TAPSE has been reported in HIV+ young adults but not in HIV− controls . Follow‐up of all participants in our study may indicate if these findings are clinically relevant as both TAPSE and FAC are more useful in longitudinal studies .…”
Section: Discussionmentioning
confidence: 74%